Intervensi Spiritual Islam dalam Menurunkan Tingkat Kecemasan: Systematic Literature Review - Abul A’la Al Maududi; Cahyati Febriana; Muhammad Rizky al Fauzan; Crys Sena Puspitasari (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
Anxiety is a prevalent mental health issue that affects psychological well-being and daily functioning. In Muslim communities, Islamic spiritual practices are commonly used as coping strategies, yet empirical evidence regarding their effectiveness in reducing anxiety has not been systematically consolidated. This study aimed to synthesize scientific evidence on Islamic spiritual interventions for anxiety reduction. A systematic literature review was conducted in accordance with PRISMA guidelines by searching Google Scholar, PubMed, ScienceDirect, and Elsevier. Observational studies published between 2019 and 2026 that examined Islamic spiritual interventions and reported anxiety outcomes were included and analyzed narratively. Ten eligible articles were identified. The review demonstrates that Islamic spiritual interventions, such as dhikr, prayer, Qur’an recitation, and Islamic spiritual counseling, are consistently associated with reductions in anxiety across diverse populations and settings. Although the magnitude of effects varied, the overall findings indicate a beneficial role of Islamic spiritual practices in anxiety management. These results suggest that Islamic spiritual interventions may be integrated as complementary approaches within mental health and public health services for Muslim populations, while further methodologically rigorous studies are required to strengthen the evidence base.